18x+15=6x(2x+3)+6x-3

Simple and best practice solution for 18x+15=6x(2x+3)+6x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18x+15=6x(2x+3)+6x-3 equation:


Simplifying
18x + 15 = 6x(2x + 3) + 6x + -3

Reorder the terms:
15 + 18x = 6x(2x + 3) + 6x + -3

Reorder the terms:
15 + 18x = 6x(3 + 2x) + 6x + -3
15 + 18x = (3 * 6x + 2x * 6x) + 6x + -3
15 + 18x = (18x + 12x2) + 6x + -3

Reorder the terms:
15 + 18x = -3 + 18x + 6x + 12x2

Combine like terms: 18x + 6x = 24x
15 + 18x = -3 + 24x + 12x2

Solving
15 + 18x = -3 + 24x + 12x2

Solving for variable 'x'.

Reorder the terms:
15 + 3 + 18x + -24x + -12x2 = -3 + 24x + 12x2 + 3 + -24x + -12x2

Combine like terms: 15 + 3 = 18
18 + 18x + -24x + -12x2 = -3 + 24x + 12x2 + 3 + -24x + -12x2

Combine like terms: 18x + -24x = -6x
18 + -6x + -12x2 = -3 + 24x + 12x2 + 3 + -24x + -12x2

Reorder the terms:
18 + -6x + -12x2 = -3 + 3 + 24x + -24x + 12x2 + -12x2

Combine like terms: -3 + 3 = 0
18 + -6x + -12x2 = 0 + 24x + -24x + 12x2 + -12x2
18 + -6x + -12x2 = 24x + -24x + 12x2 + -12x2

Combine like terms: 24x + -24x = 0
18 + -6x + -12x2 = 0 + 12x2 + -12x2
18 + -6x + -12x2 = 12x2 + -12x2

Combine like terms: 12x2 + -12x2 = 0
18 + -6x + -12x2 = 0

Factor out the Greatest Common Factor (GCF), '6'.
6(3 + -1x + -2x2) = 0

Factor a trinomial.
6((1 + -1x)(3 + 2x)) = 0

Ignore the factor 6.

Subproblem 1

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Subproblem 2

Set the factor '(3 + 2x)' equal to zero and attempt to solve: Simplifying 3 + 2x = 0 Solving 3 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 0 + -3 2x = 0 + -3 Combine like terms: 0 + -3 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5

Solution

x = {1, -1.5}

See similar equations:

| 10/7=2x+4 | | 20=-16t+45t+6 | | 2-5y+z=-10 | | 7-2x^2=8x+14 | | y+24=3 | | 7(y-8)+24=10(y-6) | | 8b-95= | | -5x+8=-3x-10 | | ln(x^2+20)=ln(9x) | | -7.9k+7.4=283.9 | | 1.9h+9.6=-53.3 | | h=-16t^2+3.5t | | 27-7e=9e | | 27-7e= | | http://compass.scsk12.org/Assess/DPT/QIEImagesStorage/HSLQ_/HSLQ_A213B01_J_stem1_1.gif | | b+6.8=46.9 | | Y+32=2y+6 | | 2.9x-1.5=13 | | 2.9x-1.6=14 | | 2.5x+43.4=50.9 | | 3qr+3t=6u | | q/7=17.5/7 | | 3x^2-65x+250=0 | | 3(x^2)-5x+.5=0 | | 10x+15y=590 | | N+-6=42 | | 7y+2(y-7)=6(y-7)-3 | | 6=-x+e | | log(x^2-25)=log(10x) | | 6x+3=12x+8 | | -11e-3=8-4e | | 4(2b-3)=3+8B-11 |

Equations solver categories